An Analytical Development To Evaliate The Influence Of Cross Phase Modulation In WDM IM/DD Transmission Systems - Putri Mariah Z.M. Ahmad Zahidin, (2003)
A detailed analytical formulation is presented to study the impact of Cross-Phase Modulation (XPM) induced phase shift on the Bit Error Rate(BER) performance of Wavelenggth Division Multiplexing(WDM) transmission system with Intensity Modulation and Direct Detection(IM/DD). The analysis is carried out to determine the influence of XPM on the pulse shape at the fiber output at the receiving end which results in inter-symbol interference(ISI)